Superior hydrogen embrittlement resistance of WAAM Ti-6Al-4V compared to wrought alloy under gaseous hydrogen charging - Kim, Soobin; Huang, Yuanjiu; Kam, Dong-Hyuck; Suh, Jin-Yoo; Lee, Kee-Ahn (Pergamon Press Ltd., 2026)
This study demonstrates the superior hydrogen embrittlement (HE) resistance of Ti-6Al-4V fabricated by wire arc additive manufacturing (WAAM) compared with its wrought counterpart under high-pressure gaseous hydrogen charging (300 °C, 15 MPa, 72 h). After hydrogen exposure, both alloys exhibited increased strength; however, their ductility responses differed significantly. The WAAM specimen retained stable tensile properties, with elongation decreasing from 9.33 % to 8.91 %, corresponding to a HE index (HEI) of only 4.5 %. In contrast, the wrought specimen showed a substantial ductility reduction, from 10.42 % to 7.73 %, resulting in an HEI of 25.8 % and indicating much higher susceptibility to embrittlement. Microstructural and crystallographic analyses revealed that the continuous α/β lamellar structure in WAAM activated hydrogen-enhanced localized plasticity (HELP) in a spatially distributed manner across multiple interfaces in conjunction with dual hydrogen-trapping states. Such interfacial dislocation activity facilitated slip transfer and alleviated strain localization, thereby enabling a more uniform macroscopic deformation response. Conversely, the wrought alloy exhibited highly localized HELP together with hydrogen-enhanced decohesion (HEDE) within the β phase, associated with a single deep trapping state that accelerated premature cracking. These results highlight that the unique interfacial network generated by WAAM mitigates hydrogen-induced damage and preserves ductility, underscoring its potential as a titanium structural material suitable for hydrogen-containing environments.